(1) 5(x-2) +(x-3) = 2(2x + 1)- answer this with full explanation
Answers
Answered by
1
Step-by-step explanation:
5(x-2)+(x-3)=2(2x+1)
We move all terms to the left:
5(x-2)+(x-3)-(2(2x+1))=0
We multiply parentheses
5x+(x-3)-(2(2x+1))-10=0
We get rid of parentheses
5x+x-(2(2x+1))-3-10=0
We calculate terms in parentheses: -(2(2x+1)), so:
2(2x+1)
We multiply parentheses
4x+2
Back to the equation:
-(4x+2)
We add all the numbers together, and all the variables
6x-(4x+2)-13=0
We get rid of parentheses
6x-4x-2-13=0
We add all the numbers together, and all the variables
2x-15=0
We move all terms containing x to the left, all other terms to the right
2x=15
x=15/2
x=7+1/2
Attachments:
![](https://hi-static.z-dn.net/files/d34/19c359a276169416d0603ec45a5ab0fe.jpg)
![](https://hi-static.z-dn.net/files/dc3/b89c6efc76ba33048e0e04a3a853b835.jpg)
Similar questions
English,
2 months ago
Social Sciences,
4 months ago
Math,
4 months ago
Science,
11 months ago
Physics,
11 months ago